Properties of magnetic paper prepared via in situ synthesis method - Rose Farahiyan Munawar; Sarani Zakaria; Shahidan Radiman; Chia, Chin Hua; Mustaffa Abdullah (Universiti Kebangsaan Malaysia, 2010)
Magnetic paper were prepared via the in situ synthesis method with ferrites in the presence of polyethylenimine (PEI). In this work, the thermomechanical pulp (TMP) fibers were used due to low percentage of collapse lumen and the large lumen size for optimum loading degree. Four cycles of the reaction were performed on the TMP fibers with pH values of 4-10. It was found that variation of pH value played an important role in the loading degree of pulp during synthesis process. The magnetic, morphological and structural properties of the magnetic paper obtained were reported. At the optimum pH of 6.0, saturation magnetization was found to be 3.08 emu/g, remainance magnetization was 0.11 emu/g and coercive force was 12.64 Oe. The optimum loading degree was found to be 23.25%.